Pengembangan Sistem Informasi Layanan Kredit Pada Unit Layanan Modal Mikro (ULaMM) Cabang Wates - Bagus Kurniawan; Niken Hendrakusma Wardani; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Unit Layanan Modal Mikro (ULaMM) is a capital loan service for micro businesses. The large number of customer members who collaborate requires ULAMM to be able to manage customer data well and provide the best service to maintain and increase customer loyalty. Problems that often occur related to data management, especially the problem of credit history and lack of delivery of credit information from UlaMM to customers. Based on the problem, it is necessary to apply Customer Relationship Management (CRM) method to Service Automation domain to manage customer service automatically by taking function of contact centers configured to communicate with customers. Development of information systems using waterfall method that starts from the needs analysis, design, implementation and testing system. Design and implementation using structural approach (Data Flow Diagram, Entity Relationship Diagram and State Transition Diagram). Implementation Information System Web-based Credit Service and SMS gateway. Test results using black-box testing shows 23 functions run well according to needs and design. Testing usability (learnability, efficiency, memorability, error, and satisfation) to the user has an average value of 4.0, this indicates that the user is easy in using Credit Information System Information.